A Literature Review on the Benefits of Acupressure Therapy in Overcoming Health Problems - Maria Komariah; Aep Maulid Mulyana; Sidik Maulana; Azzah Dinah Rachmah; Fauziah Nuraeni (Jurnal Medika Hutama, 2021)
Background: Non-pharmacological treatment is a type of complementary medicine. Acupressure therapy is a type of complementary therapy that includes massage and stimulation of specific points on the body, as well as simple and effective actions. At the moment, little is known about the health benefits of acupressure. As a result, the purpose of this study is to conduct a literature review on the use of acupressure therapy in the treatment of various health problems. Methods: A literature review was conducted using the Google Scholar and Pubmed electronic databases, with a time span of 2013-2020 and the keywords effectiveness, complementary therapy, acupressure, health, and disease. This study's eligibility criteria are Indonesian and English journal articles. The obtained articles were descriptively analyzed. Results: The author received 24 articles out of a total of 23,185 articles collected. According to the findings of the literature review, acupressure therapy has a significant effect size in reducing several health problems, including overcoming dysmenorrhea, overcoming depression, anxiety, and stress, overcoming stress and sleep status, relieving post-partum pain, reducing nausea and vomiting, frequency of enuresis, and reducing pressure. blood pressure, the severity of restless leg syndrome, headache levels, and type 2 diabetes mellitus Conclusion: Acupuncture therapy has numerous health benefits, particularly in the reduction of pain, chronic diseases, psychology, neurology, and various disease symptoms.